2020
DOI: 10.1002/jper.20-0560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of length and location of the maxillary sinus intraosseous artery using computerized tomography

Abstract: Background The intraosseous artery is a branch of the posterior superior alveolar artery that supplies the lateral wall of the maxillary sinus. The present study seeks to analyze the location of the intraosseous artery and its site of termination. Methods Cone beam computed tomography was used to evaluate 200 patients making up 400 maxillary sinuses. The following criteria were measured: (1) the distance of the lower border of the intraosseous artery to the floor of the sinus, (2) the average length of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“… Pandharbale et al, 2016 , Yang and Kye, 2014 , and Tran et al (2021) reported no statistical differences in the measurements between male and female populations, a finding that we concur with. In contrast, Laovoravit et al, 2021 , Karslioglu et al, 2020 reported that the distance from the artery to the floor of the maxillary sinus was greater in males compared to females.…”
Section: Discussionsupporting
confidence: 90%
“… Pandharbale et al, 2016 , Yang and Kye, 2014 , and Tran et al (2021) reported no statistical differences in the measurements between male and female populations, a finding that we concur with. In contrast, Laovoravit et al, 2021 , Karslioglu et al, 2020 reported that the distance from the artery to the floor of the maxillary sinus was greater in males compared to females.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies initially seemed to meet the inclusion criteria but were ultimately excluded. These included studies utilizing radiographs other than CBCT, 22 42 43 44 45 46 47 48 49 50 51 studies with internal inconsistencies related to their reported results 52 53 , those that did not investigate the PSAA as a whole unit (for instance, only analyzing a branch of the PSAA), 36 54 55 56 57 58 and those that did not analyze at least 1 PSAA characteristic pertinent to the present inclusion criteria. 59 60 …”
Section: Resultsmentioning
confidence: 99%
“…As regards the mean diameters, Yusof et al [ 38 ] reported that in the dentate patients, the mean caliber was 1.4 mm, and in edentulous patients, 1.0 mm. Albuquerque et al [ 39 ], Alves et al [ 40 ], Dias et al [ 41 ], Padovani et al [ 42 ], and Tran et al [ 43 ] in 2020 found a frequency of 88.5%, 89.3%, 56.2%, 76.7%, and 84%, respectively. As regards the parameter of the mean diameter, Albuquerque et al found a measure of 1.32 mm, while Alves et al found a measure of 1.16 mm, and Tran et al [ 43 ] found an average diameter of 0.91 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Albuquerque et al [ 39 ], Alves et al [ 40 ], Dias et al [ 41 ], Padovani et al [ 42 ], and Tran et al [ 43 ] in 2020 found a frequency of 88.5%, 89.3%, 56.2%, 76.7%, and 84%, respectively. As regards the parameter of the mean diameter, Albuquerque et al found a measure of 1.32 mm, while Alves et al found a measure of 1.16 mm, and Tran et al [ 43 ] found an average diameter of 0.91 mm. Finally, in 2021, Fayek et al [ 44 ] and Godil et al [ 45 ] found a frequency of 92% with a mean diameter of 1.0 mm and a frequency of 99.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%